PENGARUH KETERTARIKAN INVESTOR ASING DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Irsalina Nur Idzni; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of foreign ownership, the number of commissioners of the board of directors or foreign, institutional ownership against corporate tax avoidance in the annual report published by companies.The population used in this study are all public companies is composed of non-financial companies listed on the Indonesia Stock Exchange in 2013 to 2015 which publishes an annual report as well as the complete financial reports. The sampling method used in this research is purposive sampling, and obtained a sample of 182 companies. This study uses the technique of multiple linear regression analysis.The results of this study indicate that foreign ownership, no positive effect on corporate tax avoidance. While the board of directors or commissioners of foreign and institutional ownership has a positive influence on corporate tax avoidance.